The Public/Private Law Dichotomy and Its Relationship with the Policy/Operational Factors Distinction in Tort Law - Deegan, Anne (Law and Justice Journal, 2020)
The critical evaluation of the High Court's decision in Crimmins v Stevedoring Industry Finance Committee in the conceptual context of the public/private law dichotomy is discussed. The public/private law dichotomy is a formalistic distinction which belies the fact that there are overlaps in public and private law and that all law is in fact guided by considerations of public policy.